Management of endocrine surgical disorders during COVID-19 pandemic: expert opinion for non-surgical options - GÖZÜ, HÜLYA; UĞURLU, MUSTAFA ÜMİT (SPRINGER-VERLAG ITALIA SRL, 2022)
Purpose The COVID-19 pandemic brought unprecedented conditions for overall health care systems by restricting resources for non-COVID-19 patients. As the burden of the disease escalates, routine elective surgeries are being cancelled. The aim of this paper was to provide a guideline for management of endocrine surgical disorders during a pandemic. Methods We used Delphi method with a nine-scale Likert scale on two rounds of voting involving 64 experienced eminent surgeons and endocrinologists who had the necessary experience to provide insight on endocrine disorder management. All voting was done by email using a standard questionnaire. Results Overall, 37 recommendations were voted on. In two rounds, all recommendations reached an agreement and were either endorsed or rejected. Endorsed statements include dietary change in primary hyperparathyroidism, Cinacalcet treatment in secondary hyperparathyroidism, alpha-blocker administration for pheochromocytoma, methimazole +/- beta-blocker combination for Graves' disease, and follow-up for fine-needle aspiration results of thyroid nodules indicated as Bethesda 3-4 cytological results and papillary microcarcinoma. Conclusion This survey summarizes expert opinion for the management of endocrine surgical conditions during unprecedented times when access to surgical treatment is severely disrupted. The statements are not applicable in circumstances in which surgical treatment is possible.
Keywords: Consensus; Endocrine disease; Expert opinion; Pandemic; Qualtrics; Survey